2013
DOI: 10.1016/j.cyto.2012.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Th1/Th2 cytokine profile in childhood-onset systemic lupus erythematosus

Abstract: Th1 cytokines may play a role in the pathogenesis of neuropsychiatric and renal manifestations in childhood-onset SLE. The correlation with SLEDAI suggests that TNF-α may be a useful biomarker for disease activity in childhood-onset SLE, however longitudinal studies are necessary to determine if increase of this cytokine may predict flares in childhood-onset SLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
3
9

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 77 publications
2
30
3
9
Order By: Relevance
“…In a Thai population, high serum levels of IL-10 and association with disease activity were reported in cSLE patients (21). In a population in southern Brazil, increased levels of IL-10 were associated with anti-dsDNA in cSLE (14 ). The majority of studies involving adult SLE patients also reported increased levels of IL-10, which were associated with disease activity and increased production of anti-dsDNA (22).…”
Section: Discussionmentioning
confidence: 99%
“…In a Thai population, high serum levels of IL-10 and association with disease activity were reported in cSLE patients (21). In a population in southern Brazil, increased levels of IL-10 were associated with anti-dsDNA in cSLE (14 ). The majority of studies involving adult SLE patients also reported increased levels of IL-10, which were associated with disease activity and increased production of anti-dsDNA (22).…”
Section: Discussionmentioning
confidence: 99%
“…Studies involving systemic lupus erythematosus (SLE) patients have reported increased numbers of Th17 cells in sera and in the biopsied tissue of individuals with kidney damage and lupus nephritis (LN) (4,5). Increased IL-17A levels have also been reported in the sera of SLE patient subsets, particularly those with LN (4)(5)(6). Furthermore, in lupus-prone mice, the over-expression of IL-17A and subsequent expansion of DN T cells in the tubulointerstitial space has been linked to the development of nephritis (4,(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 98%
“…16-18 (ii) In many illnesses and conditions, cytokine levels are cross-sectionally associated with depression risk. 19-21 This includes coronary disease, 22-26 cancer, 27-32 infectious illness, 33-36 multiple sclerosis, 37 dermatitis, 38, 39 lupus, 40, 41 kidney disease, 42, 43 chronic alcohol use, 44, 45 pregnancy, 46, 47 etc. Among each of these conditions, depressed patients tend to have higher levels of inflammatory cytokines.…”
mentioning
confidence: 99%